2010
DOI: 10.1097/jgp.0b013e3181cc037b
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Outcomes for Depressed and Nondepressed Older Adults in Community Long-Term Care

Abstract: Structured AbstractObjective-To compare outcomes of mortality, institutionalization, physical and mental quality of life, overall life satisfaction, and satisfaction with living arrangements, for depressed and nondepressed clients after one-year of community long-term care (CLTC) services.Design-Prospective cohort study with repeated assessments at 6 and 12 months.Setting-A publicly-funded CLTC agency that coordinates in-home care such as meal delivery, personal care and nursing care to functionally disabled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
3
25
0
1
Order By: Relevance
“…Generally, most of the generic HQOL domains were affected in a negative way by a depressive disorder or a severe degree of depressive symptoms, except for physical functioning (role limitations due to physical health) and in the mental domain (emotional, psychological functioning) [3,10,21,25,45,82]. Two studies found that general health and vitality (and energy level) were not affected by depression [2,21] while spiritual, body pain, and satisfaction with living arrangements domains were not affected by depression in 1 study each [2,25,45].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, most of the generic HQOL domains were affected in a negative way by a depressive disorder or a severe degree of depressive symptoms, except for physical functioning (role limitations due to physical health) and in the mental domain (emotional, psychological functioning) [3,10,21,25,45,82]. Two studies found that general health and vitality (and energy level) were not affected by depression [2,21] while spiritual, body pain, and satisfaction with living arrangements domains were not affected by depression in 1 study each [2,25,45].…”
Section: Resultsmentioning
confidence: 99%
“…In all, 45 studies reported that they excluded individuals with cognitive impairment or a diagnosis of dementia, of which 30 were cross-sectional studies (58.8%) [11,12,17,19,24,30,31,32,33,37,58,59,60,62,63,64,65,66,69,72,73,75,76,77,78,88,89,90,91,92] and 15 were longitudinal studies (68.2%) [2,3,4,8,10,18,20,21,25,26,34,45,46,48,49]. Cognitive function was equally assessed in clinical studies (n = 11) and in community-based studies (n = 12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pearson's correlation test was used to assess the correlation between the variables (e.g., between GFI score and MAI score). The potential covariates were selected based on a priori knowledge or their association with main variables (e.g., frailty) [44,45,46,47,48]. …”
Section: Methodsmentioning
confidence: 99%